Evolution and conjugating model of carbonic material thermochemical conversion using a nonisothermal kinetic approach - S. I. Tsyganova; Tsyganov, A. D. (ՀՀ ԳԱԱ հրատ.)
The evolution of carbonic material thermochemical conversion and the associative conjugating model are presented by the example of pitch carbonization to see the development of the complex system on the whole. Methodological approach is suggested to simplify the kinetics of complicated processes during heating and to calculate apparent activation energies of the product formation processes at various temperatures. The diagnostics of pitch thermochemical conversion is carried out from the point of view of evolutional conjugated pathway of the complex system development.
Keywords: Քիմիա